Barriers and enablers to climate change adaptation in hierarchical gov ernance systems: the case of Vietnam - Phuong, Le Thi Hong; Biesbroek, G. Robbert; Wals, Arjen E. J. (Journal of Environmental Policy & Planning, 2018)
Governments fulfil important roles in increasing the adaptive capacity of local communities to respond to climate change impacts, particular ly in developing countries. Existing studies on how governments enable and constrain the ways in which local level communities learn and bui ld their adaptive capacity, however, generally adopt network or market -oriented types of governance. However, the most vulnerable regions to climate change impact in the world are generally governed through hie rarchical policy systems. This research aims to understand how the hie rarchical policy system in Vietnam creates enables and/or constrains t he policy capacity of policy actors to contribute to effective climate change adaptation. We conducted interviews (n = 26) with key actors a t multiple levels of government. Our findings show the importance of c lear legal institutions, available financing for implementing policies , and the training of governmental staff, particularly at district and commune levels where the policy capacities are generally too low to d eal with climate change impacts. We conclude that any efforts to suppo rt local actors (i.e. smallholder farmers) should include investments in policy capacity to ensure uptake and upscaling of adaptation action s more broadly.